Platinum-free high-entropy alloy catalyst as well as preparation method and application thereof
By developing platinum-free high-entropy alloy catalysts, the existing platinum materials are solved, and the problem of high cost and susceptible to impurities in fuel cells is achieved, achieving efficient, low-cost and environmentally friendly catalyst applications.
Patent Information
- Application Number
- CN202311386241.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-24
- Publication Date
- 2025-04-25
AI Technical Summary
Platinum materials commonly used in existing fuel cell catalysts are difficult to widely use because of their high price, scarcity, susceptible to impurities and reduced catalytic activity.
A platinum-free high-entropy alloy catalyst was developed, including support such as reduced graphene oxide and carbon black, as well as high-entropy alloys such as chromium, zirconium, titanium, vanadium, copper, iron, cobalt, nickel, aluminum and manganese, and prepared by ultrasonic oscillation, microwave irradiation and centrifugal filtration.
This catalyst reduces the cost of the fuel cell system, has higher endurance, efficiency and stability, and has low environmental pollution, so it can maintain good catalytic activity under actual operating conditions.
Smart Images

Figure BDA0004512619650000101 
Figure BDA0004512619650000102 
Figure HDA0004512620220000011
Abstract
Description
Technical Field
[0001] The invention relates to a high entropy alloy catalyst, in particular to a platinum-free high entropy alloy catalyst, a preparation method thereof and application thereof. Background Art
[0002] Common alternative energy sources include wind power generation limited by climate, hydropower generation limited by terrain, and solar power generation limited by climate or season. Fuel cells are a more promising alternative energy source because they are not affected by climate, terrain, season, and other factors.
[0003] Currently, catalysts such as platinum (Pt) are often used in fuel cells such as proton exchange membrane fuel cells (PEMFC) and direct methanol fuel cells (DMFC). However, platinum is expensive and rare, making it difficult to be widely used in fuel cells; obtaining platinum has a negative impact on the environment; over time, especially under severe operating conditions, platinum will degrade, causing its catalytic activity to decrease; platinum is easily affected by impurities such as carbon monoxide in fuel cells (impurities are toxic to catalysts), resulting in reduced catalytic activity. Therefore, the problem of how to prepare low-cost, high-endurance, high-performance and low-pollution catalysts has been widely studied. Summary of the invention
[0004] The present invention is completed in view of the above problems, and its purpose is to provide a platinum-free high entropy alloy catalyst and a method for quickly preparing the platinum-free high entropy alloy catalyst. In addition, the present invention also aims to provide an application using the platinum-free high entropy alloy catalyst.
[0005] The first aspect of the present invention provides a platinum-free high entropy alloy catalyst, comprising: a carrier comprising reduced graphene oxide (rGO) and carbon black (CB); and a high entropy alloy located on the carrier; wherein the high entropy alloy comprises chromium, zirconium, titanium, vanadium, copper, iron, cobalt, nickel, aluminum and manganese; wherein the high entropy alloy does not contain platinum.
[0006] The second aspect of the present invention provides a method for preparing a platinum-free high entropy alloy catalyst, comprising: adding graphene oxide (GO), carbon black and ethylene glycol to a solution containing a plurality of metal ions to obtain a precursor solution, wherein the plurality of metal ions include chromium ions, zirconium ions, titanium ions, vanadium ions, copper ions, iron ions, cobalt ions, nickel ions, aluminum ions and manganese ions, but do not include platinum ions; placing the precursor solution in an ultrasonic water bath for ultrasonic oscillation to prepare a homogeneous slurry and adjusting the homogeneous slurry to alkalinity; using a pulsed microwave reactor to irradiate the homogeneous slurry with microwaves; centrifuging the homogeneous slurry to obtain a crude product; and drying the crude product to obtain a platinum-free high entropy alloy catalyst. In other embodiments of the present invention, the weight ratio of the graphene oxide and the carbon black can be (0.3 to 3): 1, for example, 3: 1, or 1: 1, or 1: 3.
[0007] A third aspect of the present invention provides an application of the aforementioned platinum-free high entropy alloy catalyst prepared by the above method in a fuel cell.
[0008] The application of the platinum-free high entropy alloy catalyst of the present invention can reduce the cost of the fuel cell system, and its various applications will be more environmentally friendly. Using it can reduce the ecological footprint of the fuel cell, it has good stability and a longer service life, and its power output can be the same as or exceed that of a platinum-containing catalyst, and impurities have little effect on it, so it can maintain good catalytic activity under actual operating conditions. Therefore, the platinum-free high entropy alloy catalyst of the present invention has lower cost, higher endurance, higher efficiency, and lower environmental pollution than a platinum-containing catalyst. The method for preparing a platinum-free high entropy alloy catalyst of the present invention can quickly prepare a platinum-free high entropy alloy catalyst.
[0009] The above description of the content of the present invention and the following description of the embodiments are for demonstrating and explaining the spirit and principle of the present invention, and provide a further explanation of the scope of the patent application of the present invention. However, it is obvious to those skilled in the art that these examples are only for illustrating the present invention and should not be construed as limiting the scope of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] Figure 1 These are XRD spectra of the platinum-free high entropy alloy catalysts prepared by the method for preparing a platinum-free high entropy alloy catalyst according to the first to third embodiments of the present invention.
[0011] FIG. 2A to FIG. 2C They are respectively the EDS analysis results of the platinum-free high entropy alloy catalysts prepared by the method for preparing a platinum-free high entropy alloy catalyst according to the first to third embodiments of the present invention.
[0012] Figure 3A It is an image of the surface of a carrier of a platinum-free high entropy alloy catalyst prepared by the method for preparing a platinum-free high entropy alloy catalyst according to the first embodiment of the present invention.
[0013] FIG. 3B to FIG. 3K This is a distribution diagram of various metal elements on the surface of a carrier of a platinum-free high entropy alloy catalyst prepared by the method for preparing a platinum-free high entropy alloy catalyst according to the first embodiment of the present invention.
[0014] Figure 4A It is an image of the surface of a carrier of a platinum-free high-entropy alloy catalyst prepared by the method for preparing a platinum-free high-entropy alloy catalyst according to the second embodiment of the present invention.
[0015] Figures 4B to 4K This is a distribution diagram of various metal elements on the surface of a carrier of a platinum-free high entropy alloy catalyst prepared by the method for preparing a platinum-free high entropy alloy catalyst according to the second embodiment of the present invention.
[0016] Figure 5A It is an image of the surface of a carrier of a platinum-free high-entropy alloy catalyst prepared by the method for preparing a platinum-free high-entropy alloy catalyst according to the third embodiment of the present invention.
[0017] FIG. 5B to FIG. 5K This is a distribution diagram of various metal elements on the surface of a carrier of a platinum-free high-entropy alloy catalyst prepared by the method for preparing a platinum-free high-entropy alloy catalyst according to the third embodiment of the present invention.
[0018] Fig. 6A These are the results of linear voltammetry of CB containing platinum according to comparative examples of the present invention.
[0019] FIG. 6B to FIG. 6D They are respectively the results of linear voltammetry of platinum-free high entropy alloy catalysts prepared by the method for preparing a platinum-free high entropy alloy catalyst according to the first to third embodiments of the present invention.
[0020] Fig. 7A Graph showing current density versus time for a platinum-containing CB according to a comparative example of the present invention.
[0021] FIG. 7B to FIG. 7D They are graphs of current density versus time of platinum-free high entropy alloy catalysts prepared according to the method for preparing a platinum-free high entropy alloy catalyst according to the first to third embodiments of the present invention. DETAILED DESCRIPTION
[0022] The detailed features and advantages of the present invention are described in detail in the embodiments below, and the contents are sufficient to enable any relevant technician to understand the technical content of the present invention and implement it accordingly, and according to the contents disclosed in this specification, the scope of the claims and the drawings, any relevant technician can easily understand the relevant purposes and advantages of the present invention. The following examples are to further describe the viewpoints of the present invention in detail, but are not to limit the scope of the present invention in any viewpoint.
[0023] Hereinafter, the platinum-free high entropy alloy catalyst, its preparation method and its application of the present invention will be described in detail with reference to the accompanying drawings.
[0024] In this article, all features or conditions defined in the form of numerical ranges or percentage ranges, such as numerical values, quantities, contents and concentrations, are only for simplicity and convenience. Thus, the description of numerical ranges or percentage ranges should be considered to have covered and specifically disclose all possible secondary ranges and individual values (including integers and decimals) within the range. For example, the range description of "1.00 to 8.00" should be considered to have specifically disclosed all secondary ranges such as 1.00 to 8.00, 1.00 to 7.00, 2.00 to 8.00, 2.00 to 6.00, 3.00 to 6.00, 4.00 to 8.00, 3.00 to 8.00, and includes endpoint values.
[0025] In one embodiment of the present invention, a platinum-free high entropy alloy catalyst comprises: a carrier comprising reduced graphene oxide and carbon black; and a high entropy alloy located on the carrier; wherein the high entropy alloy comprises chromium, zirconium, titanium, vanadium, copper, iron, cobalt, nickel, aluminum and manganese; wherein the high entropy alloy does not contain platinum
[0026] In another embodiment of the present invention, the high entropy alloy may include 5.59at.% to 13.61at.% (atomic percentage) chromium, 15.38at.% to 19.79at.% zirconium, 1.09at.% to 11.72at.% titanium, 5.51at.% to 12.35at.% vanadium, 7.47at.% to 12.62at.% copper, 8.88at.% to 17.74at.% iron, 10.93at.% to 14.61at.% cobalt, 9.91at.% to 14.03at.% nickel, 2.24at.% to 10.39at.% aluminum and 4.66at.% to 8.77at.% manganese, and does not include platinum. In other embodiments of the present invention, the weight ratio of the reduced graphene oxide and the carbon black can be (0.3 to 3): 1, for example, it can be 3: 1, or 1: 1, or 1: 3.
[0027] In another embodiment of the present invention, the high entropy alloy may contain 5.73at.% to 13.28at.% chromium, 15.77at.% to 19.31at.% zirconium, 1.12at.% to 11.43at.% titanium, 5.65at.% to 12.05at.% vanadium, 7.66at.% to 12.31at.% copper, 9.11at.% to 17.31at.% iron, 11.21at.% to 14.25at.% cobalt, 10.16at.% to 13.69at.% nickel, 2.30at.% to 10.14at.% aluminum and 4.78at.% to 8.56at.% manganese.
[0028] In another embodiment of the present invention, the high entropy alloy may include 13.28 at.% chromium, 15.77 at.% zirconium, 1.89 at.% titanium, 5.65 at.% vanadium, 7.66 at.% copper, 14.71 at.% iron, 14.25 at.% cobalt, 11.87 at.% nickel, 10.14 at.% aluminum and 4.78 at.% manganese.
[0029] In another embodiment of the present invention, the high entropy alloy may contain 5.73at.% chromium, 16.41at.% zirconium, 1.12at.% titanium, 12.05at.% vanadium, 8.68at.% copper, 17.31at.% iron, 11.21at.% cobalt, 13.69at.% nickel, 5.24at.% aluminum and 8.56at.% manganese.
[0030] In another embodiment of the present invention, the high entropy alloy may contain 8.89at.% chromium, 19.31at.% zirconium, 11.43at.% titanium, 8.89at.% vanadium, 12.31at.% copper, 9.11at.% iron, 12.30at.% cobalt, 10.16at.% nickel, 2.30at.% aluminum and 5.30at.% manganese.
[0031] In one embodiment of the present invention, a method for preparing a platinum-free high entropy alloy catalyst comprises: adding graphene oxide, carbon black and ethylene glycol to a solution containing a plurality of metal ions to obtain a precursor solution, wherein the plurality of metal ions include chromium ions, zirconium ions, titanium ions, vanadium ions, copper ions, iron ions, cobalt ions, nickel ions, aluminum ions and manganese ions, but not platinum ions; placing the precursor solution in an ultrasonic water bath for ultrasonic oscillation to prepare a homogeneous slurry and adjusting the homogeneous slurry to alkalinity; using a pulsed microwave reactor to irradiate the homogeneous slurry with microwaves; centrifuging the homogeneous slurry to obtain a crude product; and drying the crude product to obtain a platinum-free high entropy alloy catalyst. In other embodiments of the present invention, the weight ratio of the graphene oxide and the carbon black can be (0.3 to 3): 1, for example, 3: 1, or 1: 1, or 1: 3.
[0032] In one embodiment of the present invention, the platinum-free high entropy alloy catalyst as described above prepared by the above method is used in a fuel cell.
[0033] The solution capable of providing Co ions used in the present invention can be other solutions known to those skilled in the art that can provide Co ions and will not react with Al ions, Ni ions, Mn ions, Fe ions, Cu ions, Ti ions, V ions, Cr ions, and Zr ions, such as precipitation reactions. Therefore, the present invention uses an aqueous solution of cobalt nitrate, but is not limited thereto.
[0034] The solution capable of providing Al ions used in the present invention can be other solutions known to those skilled in the art that can provide Al ions and will not react with Co ions, Ni ions, Mn ions, Fe ions, Cu ions, Ti ions, V ions, Cr ions, and Zr ions, such as precipitation reactions. Therefore, the present invention uses an aqueous solution of aluminum nitrate, but is not limited thereto.
[0035] The solution capable of providing Ni ions used in the present invention can be other solutions known to those skilled in the art that can provide Ni ions and will not react with Co ions, Al ions, Mn ions, Fe ions, Cu ions, Ti ions, V ions, Cr ions, and Zr ions, such as precipitation reactions. Therefore, the present invention uses a nickel nitrate aqueous solution, but is not limited thereto.
[0036] The solution capable of providing Mn ions used in the present invention can be other solutions known to those skilled in the art that can provide Mn ions and will not react with Co ions, Al ions, Ni ions, Fe ions, Cu ions, Ti ions, V ions, Cr ions, and Zr ions, such as precipitation reactions. Therefore, the present invention uses an aqueous solution of manganese nitrate, but is not limited thereto.
[0037] The solution capable of providing Fe ions used in the present invention can be other solutions known to those skilled in the art that can provide Fe ions and will not react with Co ions, Al ions, Ni ions, Mn ions, Cu ions, Ti ions, V ions, Cr ions, and Zr ions, such as precipitation reactions. Therefore, the present invention uses an aqueous solution of ferric nitrate, but is not limited thereto.
[0038] The solution capable of providing Cu ions used in the present invention can be other solutions known to those skilled in the art that can provide Cu ions and will not react with Co ions, Al ions, Ni ions, Mn ions, Fe ions, Ti ions, V ions, Cr ions, and Zr ions, such as precipitation reactions. Therefore, the present invention uses a copper sulfate aqueous solution, but is not limited thereto.
[0039] The solution capable of providing Ti ions used in the present invention can be other solutions known to those skilled in the art that can provide Ti ions and will not react with Co ions, Al ions, Ni ions, Mn ions, Fe ions, Cu ions, V ions, Cr ions, and Zr ions, such as precipitation reactions. Therefore, the present invention uses a titanium dioxide aqueous solution, but is not limited thereto.
[0040] The solution capable of providing V ions used in the present invention can be other solutions known to those skilled in the art that can provide V ions and will not react with Co ions, Al ions, Ni ions, Mn ions, Fe ions, Cu ions, Ti ions, Cr ions, and Zr ions, such as precipitation reactions. Therefore, the present invention uses a vanadium pentoxide aqueous solution, but is not limited thereto.
[0041] The solution capable of providing Cr ions used in the present invention can be other solutions known to those skilled in the art that can provide Cr ions and will not react with Co ions, Al ions, Ni ions, Mn ions, Fe ions, Cu ions, Ti ions, V ions, and Zr ions, such as precipitation reactions. Therefore, the present invention uses an aqueous solution of chromium chloride, but is not limited thereto.
[0042] The solution capable of providing Zr ions used in the present invention can be other solutions known to those skilled in the art that can provide Zr ions and will not react with Co ions, Al ions, Ni ions, Mn ions, Fe ions, Cu ions, Ti ions, V ions, and Cr ions, such as precipitation reactions. Therefore, the present invention uses an aqueous zirconium tetrachloride solution, but is not limited thereto.
[0043] Next, the preparation method of the platinum-free high entropy alloy catalyst of the present invention, its performance measurement results, and its application are described.
[0044] [Preparation steps of platinum-free high entropy alloy catalyst]
[0045] The preparation process of the platinum-free high entropy alloy (HEA) catalyst used in the present invention, for example, includes the following steps: cobalt (II) nitrate hexahydrate (Co(NO3)2·6H2O), aluminum nitrate nonahydrate (Al(NO3)3·9H2O), nickel (II) nitrate hexahydrate (Ni(NO3)2·6H2O), manganese (II) nitrate tetrahydrate (Mn(NO3)2·4H2O), iron (III) nitrate nonahydrate (Fe(NO3)3·9H2O), copper sulfate pentahydrate (CuSO4·5H2O), dihydrate (Mn(NO3)2·4H2O), and dihydrate (Mn(NO3)2·4H2O) are prepared. Each of the group consisting of titanium oxide (TiO2), vanadium pentoxide (V2O5), chromium (III) chloride hexahydrate (CrCl3·6H2O) and zirconium tetrachloride (ZrCl4) was dissolved in 50 milliliters (mL) of deionized water to a concentration of 0.04 M. 2 mL of each of the group treated in the above steps was added to the same sample bottle (i.e., the molar number of each metal ion in the sample bottle was the same) to obtain a solution; then 30 mL of ethylene glycol (EG) was added to the sample bottle; a total of 100 milligrams (mg) of GO and CB were added to the sample bottle (the weights of GO and CB used will be described in detail in the subsequent examples); the sample bottle was placed in an ultrasonic water bath (ultrasonic The method comprises the steps of: shaking a bath (200 μL) for 30 minutes to prepare a homogeneous slurry; adding 0.04 M potassium hydroxide (KOH) to the homogeneous slurry to adjust the pH value of the homogeneous slurry to 11.7; irradiating the shaken homogeneous slurry with microwaves for 5 minutes using a pulsed microwave reactor with a power of 700 watts (W) to 720 watts (W) and a frequency of 2.45 gigahertz (GHz) (the microwave irradiation mode is to turn on for 3 seconds and then turn off for 2 seconds as one cycle, that is, there will be a 2-second window period after the slurry is irradiated with microwaves for 3 seconds, and the cycle is repeated 60 times) to provide energy for reducing metal ions; at this time, the graphene oxide will be reduced to reduced graphene oxide; centrifuging the homogeneous slurry to obtain a crude product; washing the crude product obtained by centrifugation with deionized water several times; placing the washed crude product in an oven and baking it at 80° C. for 1 hour to remove residual moisture to obtain a platinum-free high entropy alloy catalyst. 25 mg of a platinum-free high entropy alloy catalyst, 300 μL of Nafion film, and 3 mL of 2-propanol were added to another sample bottle; the other sample bottle was placed in an ultrasonic bath for 30 minutes; and the sample in the shaken sample bottle was dropped onto carbon paper by a drop coating method for subsequent application.
[0046] [Example]
[0047] [Table 1] Weight of GO and CB used in the carrier of each example
[0048] The weight of GO CB weight First embodiment 75mg 25mg Second embodiment 50mg 50mg Third embodiment 25mg 75mg
[0049] The platinum-free high entropy alloy catalysts of the first to third embodiments are obtained by referring to the above-mentioned platinum-free high entropy alloy catalyst preparation steps and Table 1. It can be seen from Table 1 that the weight ratio of GO to CB used in the carrier of the first embodiment is 3:1, the weight ratio of GO to CB used in the carrier of the second embodiment is 1:1, and the weight ratio of GO to CB used in the carrier of the third embodiment is 1:3.
[0050] [Experiment 1] X-ray diffraction (XRD) was used to detect the characteristics of the platinum-free high entropy alloy catalyst of each example.
[0051] Please refer to Figure 1 , Figure 1 is the XRD diagram of the platinum-free high entropy alloy catalyst prepared by the method for preparing a platinum-free high entropy alloy catalyst according to the present invention in the first to third embodiments. Figure 1 It is known that the X-ray spectra of the platinum-free high entropy alloy catalysts of the first to third embodiments have a peak on the (002) plane, and since the platinum-free high entropy alloy catalysts of the first to third embodiments have a peak only at an angle of about 26 degrees, they are amorphous.
[0052] [Test 2] Analyzing the atomic percentage of metal elements in the platinum-free high entropy alloy catalyst of each example using energy-dispersive X-ray spectroscopy (EDS)
[0053] [Table 2] Results of EDS analysis of the platinum-free high entropy alloy catalysts of various examples
[0054] First Example (at.%) Second Example (at.%) Third Example (at.%) Cr 13.28 5.73 8.89 Zr 15.77 16.41 19.31 Ti 1.89 1.12 11.43 V 5.65 12.05 8.89 Cu 7.66 8.68 12.31 Fe 14.71 17.31 9.11 Co 14.25 11.21 12.30 Ni 11.87 13.69 10.16 Al 10.14 5.24 2.30 Mn 4.78 8.56 5.30 Total (at.%) 100.00 100.00 100.00
[0055] Please refer to FIG. 2A to FIG. 2C And Table 2, FIG. 2A to FIG. 2C Table 2 is the results of EDS analysis of the platinum-free high entropy alloy catalysts prepared by the method for preparing a platinum-free high entropy alloy catalyst according to the present invention in each embodiment. The atomic percentage (at.%) is the ratio of the number of atoms of a certain metal element on the carrier of the platinum-free high entropy alloy catalyst to the number of atoms of all metal elements on the carrier. It can be calculated by FIG. 2A to FIG. 2CThe area of each metal element in the spectrum of each embodiment in Table 2 is used to calculate the atomic percentage of each metal element in the carrier of the platinum-free high entropy alloy catalyst of each embodiment. If the area of a certain metal element in the spectrum is larger, it means that its atomic percentage is larger. Although the same mole (mol) number of metal ions is added in the preparation step of the platinum-free high entropy alloy catalyst, after EDS analysis, the atomic percentage of each metal element in the platinum-free high entropy alloy catalyst is different. This is caused by the different weight ratios of GO and CB used in each embodiment, because when synthesized using a pulsed microwave reactor, the different weight ratios of GO and CB will affect its ability to adsorb metal elements, resulting in different atomic percentages of each metal element in the platinum-free high entropy alloy catalyst prepared by the present invention.
[0056] [Test 3] Observation of the surface of the platinum-free high entropy alloy catalyst of each embodiment using a scanning electron microscope (SEM)
[0057] Please refer to FIG. 3A to FIG. 3K , Figure 3A is an image of the surface of a carrier of a platinum-free high-entropy alloy catalyst prepared by the method for preparing a platinum-free high-entropy alloy catalyst according to the first embodiment of the present invention, FIG. 3B to FIG. 3K This is a distribution diagram of various metal elements on the surface of a carrier of a platinum-free high entropy alloy catalyst prepared by the method for preparing a platinum-free high entropy alloy catalyst according to the first embodiment of the present invention. It can be seen that the various metal elements on the surface of the platinum-free high entropy alloy catalyst are evenly distributed.
[0058] Please refer to Figures 4A to 4K , Figure 4A is an image of the surface of a carrier of a platinum-free high-entropy alloy catalyst prepared by the method for preparing a platinum-free high-entropy alloy catalyst according to the second embodiment of the present invention, Figures 4B to 4K This is a distribution diagram of various metal elements on the surface of a carrier of a platinum-free high entropy alloy catalyst prepared by the method for preparing a platinum-free high entropy alloy catalyst according to the second embodiment of the present invention. It can be seen that the various metal elements on the surface of the platinum-free high entropy alloy catalyst are evenly distributed.
[0059] Please refer to FIG. 5A to FIG. 5K , Figure 5A is an image of the surface of a carrier of a platinum-free high-entropy alloy catalyst prepared by the method for preparing a platinum-free high-entropy alloy catalyst according to the third embodiment of the present invention, FIG. 5B to FIG. 5K This is a distribution diagram of various metal elements on the surface of a carrier of a platinum-free high entropy alloy catalyst prepared by the method for preparing a platinum-free high entropy alloy catalyst according to the third embodiment of the present invention. It can be seen that the various metal elements on the surface of the platinum-free high entropy alloy catalyst are evenly distributed.
[0060] [Test 4] Using Linear Voltammetry (LSV) to Detect the Catalytic Activity of Platinum-Containing CB and Platinum-Free High Entropy Alloy Catalysts of Each Example
[0061] [Table 3] Maximum current density of oxygen reduction reaction (ORR) and maximum current density of oxygen evolution reaction (OER) of comparative examples and examples detected by LSV
[0062]
[0063] Please refer to FIG. 6A to FIG. 6D , Fig. 6A is the result of linear voltammetry of the platinum-containing CB of the comparative example, FIG. 6B to FIG. 6D These are the results of linear voltammetry of the platinum-free high entropy alloy catalysts prepared in various embodiments according to the method for preparing a platinum-free high entropy alloy catalyst of the present invention. FIG. 6A to FIG. 6D The results are obtained by placing the platinum-containing CB of the comparative example and the platinum-free high entropy alloy catalyst of each embodiment into a 0.1M KOH solution and measuring in a pure oxygen environment. The potential range scanned in this experiment is -1.2V to 1.2V (vsAg / AgCl), but is not limited to this. The scanning rate of this experiment is 50mV / s, but is not limited to this.
[0064] The greater the redox current density, the better the catalytic activity. As can be seen from Table 3, the maximum current densities of ORR and OER in the first to third embodiments are greater than the maximum current densities of ORR and OER in the comparative example. Therefore, the platinum-free high entropy alloy catalyst prepared by the present invention has better catalytic activity than the platinum-containing catalyst.
[0065] [Test 5] Current density versus time
[0066] [Table 4]
[0067]
[0068]
[0069] Please refer to FIG. 7A to FIG. 7D , Fig. 7A is a graph of current density versus time for a platinum-containing CB of a comparative example, FIG. 7B to FIG. 7D 3 is a graph of current density versus time of a platinum-free high entropy alloy catalyst prepared according to the method for preparing a platinum-free high entropy alloy catalyst of the present invention in each embodiment. FIG. 7A to FIG. 7DThe results are obtained by placing the platinum-containing CB of the comparative example and the platinum-free high entropy alloy catalyst of each example into a 0.1M KOH solution and measuring them in a pure oxygen environment for 6 hours.
[0070] exist FIG. 7A to FIG. 7D In the process, the current density decreases rapidly because impurities such as carbon monoxide will combine with the catalyst and reduce the catalytic activity of the catalyst. When the impurities combine with the catalyst to reach equilibrium, the current density drops to the limiting current density. The larger the limiting current density, the better the catalytic activity. As can be seen from Table 4, the limiting current density of the first to third embodiments is greater than the limiting current density of the comparative example. In particular, the limiting current density of the first embodiment is about 15 times the limiting current density of the comparative example, and the limiting current density of the second embodiment is about 12 times the limiting current density of the comparative example. Therefore, the platinum-free high entropy alloy catalyst prepared by the present invention has better anti-toxicity than the platinum-containing catalyst.
[0071] The application of the platinum-free high entropy alloy catalyst of the present invention can reduce the cost of the fuel cell system, and its various applications will be more environmentally friendly. Using it can reduce the ecological footprint of the fuel cell, it has good stability and a longer service life, and its power output can be the same as or exceed that of a platinum-containing catalyst, and impurities have little effect on it, so it can maintain good catalytic activity under actual operating conditions. Therefore, the platinum-free high entropy alloy catalyst of the present invention has lower cost, higher endurance, higher efficiency, and lower environmental pollution than platinum-containing catalysts. The method for preparing a platinum-free high entropy alloy catalyst of the present invention can quickly prepare a platinum-free high entropy alloy catalyst.
Claims
1. A platinum-free high entropy alloy catalyst comprising: a support comprising reduced graphene oxide and carbon black; and A high entropy alloy is disposed on the carrier; in, The high entropy alloy comprises chromium, zirconium, titanium, vanadium, copper, iron, cobalt, nickel, aluminum and manganese; Wherein, the high entropy alloy does not contain platinum.
2. The platinum-free high entropy alloy catalyst according to claim 1, wherein The high entropy alloy contains 5.59at.% to 13.61at.% (atomic percentage) chromium, 15.38at.% to 19.79at.% zirconium, 1.09at.% to 11.72at.% titanium, 5.51at.% to 12.35at.% vanadium, 7.47at.% to 12.62at.% copper, 8.88at.% to 17.74at.% iron, 10.93at.% to 14.61at.% cobalt, 9.91at.% to 14.03at.% nickel, 2.24at.% to 10.39at.% aluminum and 4.66at.% to 8.77at.% manganese.
3. The platinum-free high entropy alloy catalyst according to claim 2, wherein: The high entropy alloy contains 5.73at.% to 13.28at.% chromium, 15.77at.% to 19.31at.% zirconium, 1.12at.% to 11.43at.% titanium, 5.65at.% to 12.05at.% vanadium, 7.66at.% to 12.31at.% copper, 9.11at.% to 17.31at.% iron, 11.21at.% to 14.25at.% cobalt, 10.16at.% to 13.69at.% nickel, 2.30at.% to 10.14at.% aluminum and 4.78at.% to 8.56at.% manganese.
4. The platinum-free high entropy alloy catalyst according to claim 3, wherein: The high entropy alloy includes 13.28 at.% chromium, 15.77 at.% zirconium, 1.89 at.% titanium, 5.65 at.% vanadium, 7.66 at.% copper, 14.71 at.% iron, 14.25 at.% cobalt, 11.87 at.% nickel, 10.14 at.% aluminum and 4.78 at.% manganese.
5. The platinum-free high entropy alloy catalyst according to claim 3, wherein: The high entropy alloy comprises 5.73 at.% chromium, 16.41 at.% zirconium, 1.12 at.% titanium, 12.05 at.% vanadium, 8.68 at.% copper, 17.31 at.% iron, 11.21 at.% cobalt, 13.69 at.% nickel, 5.24 at.% aluminum and 8.56 at.% manganese.
6. The platinum-free high entropy alloy catalyst according to claim 3, wherein: The high entropy alloy comprises 8.89 at.% chromium, 19.31 at.% zirconium, 11.43 at.% titanium, 8.89 at.% vanadium, 12.31 at.% copper, 9.11 at.% iron, 12.30 at.% cobalt, 10.16 at.% nickel, 2.30 at.% aluminum and 5.30 at.% manganese.
7. The platinum-free high entropy alloy catalyst according to any one of claims 1 to 6, wherein The weight ratio of the reduced graphene oxide to the carbon black is (0.3 to 3):
1.
8. A method for preparing the platinum-free high entropy alloy catalyst according to any one of claims 1 to 7, comprising: adding graphene oxide, carbon black and ethylene glycol to a solution containing a plurality of metal ions to obtain a precursor solution, wherein the plurality of metal ions include chromium ions, zirconium ions, titanium ions, vanadium ions, copper ions, iron ions, cobalt ions, nickel ions, aluminum ions and manganese ions, but do not include platinum ions; Placing the precursor solution in an ultrasonic water bath for ultrasonic oscillation to prepare a homogeneous slurry and adjusting the homogeneous slurry to be alkaline; irradiating microwaves to the homogeneous slurry using a pulsed microwave reactor; Centrifugally filtering the homogeneous slurry to obtain a crude product; and The crude product is dried to obtain a platinum-free high entropy alloy catalyst.
9. The method for preparing a platinum-free high entropy alloy catalyst according to claim 8, wherein: The weight ratio of the graphene oxide to the carbon black is (0.3 to 3):
1.
10. Use of the platinum-free high entropy alloy catalyst according to any one of claims 1 to 7 in a fuel cell.